METHODOLOGICAL APPROACHES TO INVESTIGATION: FROM DIALOGUE TO POLITICAL DIALOGUE - Fomina, Marina; Borisenko, Olga (European Scientific Journal, ESJ, 2013)
This article investigates the political dialogue and its methodology. The author of this article focuses their attention on the works of Feuerbach, V. Bibler, M. Buber, and M. Bakhtin; thus this allows them to identify the methodological approaches towards the study of political dialogue. Therefore, the idea of dialogue as a method of philosophizing was presented in the philosophy of Ludwig Feuerbach. He is interested in a dialogue that allows the identification of cultural and social rights, at the expense of a particular relationship of "I" to "You"; and opposes the logic of Hegel’s monologue. Thinkers cannot engage in dialogue with themselves and as such, the process of communication is necessary for the formation of humans. Thus, the transcendental dialogue provides not only an expression of thought, but it is an act of "making" and also, it is the epitome of the word.